1995
DOI: 10.1007/bf02245590
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, anxiety and vocalizations in animals: GABAA and 5-HT anxiolytics

Abstract: A continuing challenge for preclinical research on anxiolytic drugs is to capture the affective dimension that characterizes anxiety and aggression, either in their adaptive forms or when they become of clinical concern. Experimental protocols for the preclinical study of anxiolytic drugs typically involve the suppression of conditioned or unconditioned social and exploratory behavior (e.g., punished drinking or social interactions) and demonstrate the reversal of this behavioral suppression by drugs acting on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
118
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(135 citation statements)
references
References 180 publications
(158 reference statements)
11
118
0
6
Order By: Relevance
“…These observations of rather unselective antiaggressive effects of 8-OH-DPAT, buspirone, and ipsapirone are in line with what has been reported before by several authors using various aggression paradigms (Tompkins et al 1980;Flannely et al 1985;Lindgren and Kantak 1987;McMillen et al 1988;Blanchard et al 1988;Nikulina 1991;Olivier et al 1994Olivier et al , 1995Sanchez and Hyttel 1994;Miczek et al 1995;Bell andHobson 1994, Muehlenkamp et al 1995). Actually, the reduction in offensive aggression by these 5-HT 1A receptor agonists is generally explained by the predominant quiescent/akinetic (i.e., the 5-HT 1A receptor-mediated behavioral syndrome) effects these compounds induce due to their high-efficacy activation of postsynaptic 5-HT 1A receptors responsible for this (Tricklebank 1985;;Scott et al 1994;Millan et al 1994).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These observations of rather unselective antiaggressive effects of 8-OH-DPAT, buspirone, and ipsapirone are in line with what has been reported before by several authors using various aggression paradigms (Tompkins et al 1980;Flannely et al 1985;Lindgren and Kantak 1987;McMillen et al 1988;Blanchard et al 1988;Nikulina 1991;Olivier et al 1994Olivier et al , 1995Sanchez and Hyttel 1994;Miczek et al 1995;Bell andHobson 1994, Muehlenkamp et al 1995). Actually, the reduction in offensive aggression by these 5-HT 1A receptor agonists is generally explained by the predominant quiescent/akinetic (i.e., the 5-HT 1A receptor-mediated behavioral syndrome) effects these compounds induce due to their high-efficacy activation of postsynaptic 5-HT 1A receptors responsible for this (Tricklebank 1985;;Scott et al 1994;Millan et al 1994).…”
Section: Discussionsupporting
confidence: 87%
“…; and 4) S-15535 attenuated the alnespirone-induced hypothermia, consistent with its postsynaptic 5-HT 1A antagonistic properties. Taking into account the rather unique pharmacological profile of S-15535, which acts as an antagonist at postsynaptic 5-HT 1A receptors and as a full agonist at 5-HT 1A autoreceptors, these data suggest that activation of 5-HT 1A autoreceptors mediate the anti-aggressive effects of 5-HT 1A ligands.The potent anti-aggressive properties of 5-HT 1A receptor agonists have consistently been reported (Tompkins et al 1980; Flannelly et al 1985;Lindgren and Kantak 1987;McMillen et al 1988;Blanchard et al 1988;Nikulina 1991;Olivier et al 1994Olivier et al , 1995Sanchez and Hyttel 1994;Miczek et al 1995;Bell and Hobson 1994, Muehlenkamp et al 1995), but evidence on whether this occurs via a pre-or postsynaptic receptor mechanism is conflicting. Thus, it has been shown that depletion of neuronal 5-HT or lesioning of presynaptic function (with PCPA or 5,7 DHT respectively) either did not change (Sijbesma et al 1991) or even potentiates (Sanchez and Hyttel 1994) the anti-aggressive effect of 5-HT 1A receptor agonists, suggesting a postsynaptic site of action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the potentially inconsistent findings is the existence of some 50-kHz chirps during aggressive encounters [51,83,96]. Indeed, Berridge [4] has questioned our ''laughter'' interpretation of 50-kHz chirps on the basis of this finding.…”
Section: Negatively Valenced Stimuli Reduce the Tickle Responsementioning
confidence: 99%
“…USVs are counted using a bat detector (Pettersson Elektronik or Ultrasound Advice) with its microphone suspended approximately 10 cm above the test container floor. A variety of other behaviors in the novel cage, body and ambient temperature, weight, and more are also measured [41,42].Initial isolation period-Isolation-induced USV has been extensively used as a marker for distress in infant rodents [31,68,75,78,116]. The actions of anxiolytic and anxiogenic compounds on USV are generally compatible with this explanation [56,68,83,116,119].…”
mentioning
confidence: 99%